Monetary policy in Sweden after the end of Bretton Woods - Emma Bylund; Jens Iversen; Anders Vredin (Sveriges Riksbank, 2024)
This paper discusses how monetary policy in Sweden has evolved since 1973. We provide a chronology of the different monetary policy regimes in place during the past fifty years and identify two main regimes, the pegged-but-adjustable exchange rate regime (1973 - 1992) and the inflation targeting regime (1993 - 2022). Inflation in Sweden has been more stable under the inflation targeting regime than under both the Bretton Woods system, and the pegged-but-adjustable exchange rate regime. GDP growth was higher and more stable during the Bretton Woods System. We argue that inflation targeting was implemented according to the simple text book version only during a short period, 1999-2007. We illustrate that economic developments in Sweden have in many respects been similar to that of Denmark. Lastly, we identify and discuss recurrent themes in the discussions of monetary policy under inflation targeting.
Keywords: E42; E52; E58; E65; 330; monetary policy; inflation targeting; exchange rate regimes